The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00384-015-2498-x
|View full text |Cite
|
Sign up to set email alerts
|

Complication and local recurrence rate after endoscopic resection of large high-risk colorectal adenomas of ≥3 cm in size

Abstract: The present study is the largest study showing complication and recurrence rates after colorectal polypectomy of advanced colorectal adenomas of ≥3 cm in size. Polyp size was identified as the most important risk factor for complications. For the first time, this study shows that the complication rate after colorectal polypectomy of large adenomas is correlated inversely with the residual and/or recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…In our cohort, lesion size was <5 mm in only two patients. Compliance with F/U may be a problem in these patients as recently shown by a retrospective study by Seidel and colleagues 22. This might result in larger residual/recurrent lesions which may impede retreatment.…”
Section: Discussionmentioning
confidence: 89%
“…In our cohort, lesion size was <5 mm in only two patients. Compliance with F/U may be a problem in these patients as recently shown by a retrospective study by Seidel and colleagues 22. This might result in larger residual/recurrent lesions which may impede retreatment.…”
Section: Discussionmentioning
confidence: 89%
“…We did not observe any deaths due to the interventions. Some studies have reported increased complication rates (bleeding and perforations) of endoscopic removal of larger lesions ≥30mm [ 12 , 23 , 26 , 35 ]. The perforation rate of our study in patients with polyps ≥40mm was similar to the perforation rate in patients with polyps of 20-40mm.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence after piecemeal EMR is a problem [2,5,12] and the risk of recurrence increases with the size of the lesion [2,3,5]. Also, incomplete adenoma resection has a significant impact on risk of interval cancer [13].…”
Section: Discussionmentioning
confidence: 99%